Bahasa Isyarat di Balik Layar: Inklusivitas Industri Perfilman Bagi Teman Tuli Indonesia - Nursari Utami Dewi; Btari Najwa Naila; Hanni Nabila Athaya; Anggi Putri Azzahra; Nana Suryana (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Inclusivity is key to creating a fair space for everyone in various fields, including deaf people, especially in the dynamic film industry. In line with this, this study aims to evaluate the level of inclusivity in Indonesian films through the representation of deaf people and the use of sign language as a means of communication. Using a quantitative-descriptive approach, data was collected through questionnaires distributed to two categories, namely the general public and the deaf community, and then analyzed descriptively. The results show that the majority of respondents consider the use of sign language in films to be an important step towards inclusive representation because the representation of deaf people and the use of sign language in Indonesian films is still far from adequate. Further assessment of the limitations of Indonesian films that raise this theme shows that there is a gap that must be addressed immediately. These findings emphasize the need for collaboration between filmmakers, the deaf community, and relevant institutions to create more equitable and accessible representation. By incorporating empathy through the use of sign language, the film industry holds the potential to reach a broader audience and actively contribute to the creation of artworks that can be enjoyed by all segments of society.